2017
DOI: 10.3389/fnagi.2017.00070
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Elevated Total Homocysteine Levels and Functional Outcome in Elderly Patients with Acute Cerebral Infarction

Abstract: Background: An elevated plasma total homocysteine (tHcy) level is an independent risk factor for vascular events. The aim of the present study was to investigate the association between tHcy levels in the acute phase of cerebral infarction and functional outcome among elderly patients.Methods: Between October 2009 and December 2012, we recruited 594 elderly patients (age > 75) with first-onset acute cerebral infarction who were consecutively admitted to the Department of Neurology of Tianjin Huanhu Hospital, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
3
15
0
2
Order By: Relevance
“…This hypothesis has been observed in several clinical studies, with the high levels of serum Hcy as independent predictors for END for stroke patients [11, 14]. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15]. Therefore, the second goal of this study was to investigate the early prognostic roles of Hcy for patients with lacunar infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been observed in several clinical studies, with the high levels of serum Hcy as independent predictors for END for stroke patients [11, 14]. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15]. Therefore, the second goal of this study was to investigate the early prognostic roles of Hcy for patients with lacunar infarction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that Hcy may be an effective biomarker for early diagnosis and prognosis of lacunar infarction. However, a recent study suggested conflicting results, demonstrating no association between elevated Hcy levels and functional outcome among elderly patients with acute cerebral infarction [15]. Importantly, no significant difference in the Hcy level was found among the Iranian population between lacunar causes and control [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased free radicals from hydrogen peroxide (H 2 O 2 ) will exacerbate endothelial dysfunction[12]. Hcy level is an important factor in predicting the prognosis of thrombolysis, which is associated with limited report on the assessment of risks in elderly patients receiving thrombolysis[13]. The results of the present study revealed that NIHSS scores were improved and high Hcy level gradually went back to normal, which was not significantly different from low Hcy level ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Corroborando com nossos dados, González et al 4 , avaliou pacientes com idade igual ou superior a 40 anos e os resultados apresentaram níveis elevados de homocisteína no grupo úlcera quando comparado ao grupo controle. A hiperhomocisteinemia associa-se com a formação de tromboembolismo arterial e venoso e aterosclerose 19,20 . A homocisteína pode estimular a oxidação da lipoproteína de baixa densidade (LDL), sendo esta condição associada a lesões endoteliais, trombogênese e aterogênese 2,8 .…”
Section: Discussionunclassified
“…A hiperhomocisteínemia é estabelecida como um fator de risco para doenças cardiovasculares 9,20 , demonstrando associação com as doenças vasculares periféricas, o que suporta a hipótese de que níveis elevados de homocisteína podem ser um marcador/indicador de alterações vasculares 6,21 .…”
Section: Discussionunclassified